A Long View of Archaeological Collections Care, Preservation, and Management. Issue 3 (August 2019) - Benden, Danielle M.; Taft, Mara C.
Abstract: Collections care practices have become professionalized in the last 30 years, in large part because of the work of organizations such as the American Alliance of Museums, the Canadian Conservation Institute, the Society for the Preservation of Natural History Collections, the American Institute for Conservation, and others in the museum sphere. Advances in preservation and management have benefited the discipline of archaeology in the field and laboratory. This thematic issue provides an updated perspective on the current happenings in the repository, highlighting innovative techniques and practices that collections specialists employ when managing the archaeological record. This article considers a macroview of the issues surrounding archaeological curation today and ponders what the future of collections preservation can and should look like. Abstract : Las prácticas de cuidado de colecciones se han profesionalizado en los últimos treinta años, en gran parte gracias a organizaciones como la Alianza Americana de Museos, el Instituto Canadiense de Conservación, la Sociedad para la Conservación de Colecciones de Historia Natural, el Instituto Americano de Conservación y otros en las esferas museísticas. Los avances en conservación y manejo han beneficiado a la disciplina de la arqueología en el campo y el laboratorio. Este número temático proporciona una perspectiva actualizada sobre las prácticas actuales en el repositorio. Destaca las técnicas innovadoras que emplean los especialistas en colecciones al gestionar el registro arqueológico y enfatiza las maneras en que el personal del repositorio puede ayudar a los arqueólogos a cumplir con sus responsabilidades con las colecciones que generan, analizan e interpretan. Este artículo considera una visión macro de la conservación arqueológica actualmente y reflexiona sobre cómo puede y debe ser el futuro de la conservación de colecciones.